High electrical conductivity and high porosity in a Guest@MOF material: evidence of TCNQ ordering within Cu3BTC2 micropores. Issue 37 (14th August 2018) - Schneider, Christian; Ukaj, Dardan; Koerver, Raimund; Talin, A. Alec; Kieslich, Gregor; Pujari, Sidharam P.; Zuilhof, Han; Janek, Jürgen; Allendorf, Mark D.; Fischer, Roland A.
Abstract : The host–guest system TCNQ@Cu3 BTC2 is a striking example of how semiconductivity can be introduced by guest incorporation in an otherwise insulating parent material. Abstract : The host–guest system TCNQ@Cu3 BTC2 (TCNQ = 7, 7, 8, 8-tetracyanoquinodimethane, BTC = 1, 3, 5-benzenetricarboxylate) is a striking example of how semiconductivity can be introduced by guest incorporation in an otherwise insulating parent material. Exhibiting both microporosity and semiconducting behavior such materials offer exciting opportunities as next-generation sensor materials. Here, we apply a solvent-free vapor phase loading under rigorous exclusion of moisture, obtaining a series of the general formula x TCNQ@Cu3 BTC2 (0 ≤ x ≤ 1.0). By using powder X-ray diffraction, infrared and X-ray absorption spectroscopy together with scanning electron microscopy and porosimetry, we provide the first structural evidence for a systematic preferential arrangement of TCNQ along the (111) lattice plane and the bridging coordination motif to two neighbouring Cu-paddlewheels, as was predicted by theory. For 1.0TCNQ@Cu3 BTC2 we find a specific electrical conductivity of up to 1.5 × 10 −4 S cm −1 whilst maintaining a high BET surface area of 573.7 m 2 g −1 . These values are unmatched by MOFs with equally high electrical conductivity, making the material attractive for applications such as super capacitors and chemiresistors. Our results represent the crucial missing link needed to firmly establish the structure–property relationship revealed in TCNQ@Cu3 BTC2, thereby creating a sound basis for using this as a design principle for electrically conducting MOFs.